Release Mathematical Model of Active Agent from Packaging Material into Food. (24th November 2013) - Huang, Xiuling; Ye, Heng; Yam, Kit L.
Abstract : Active packaging is an innovative packaging technology by which active compounds are released from the package to enhance the quality and microbial safety for a wide range of foods. The problem of active ingredient release through the bilayer packaging food system is studied from a theoretical viewpoint. A release model is built to provide predictions of concentration and amount of active ingredient. The equations are built based on Fickian diffusion, and numerical solutions are obtained through finite difference. Different diffusion coefficients D P and D C of active ingredient in different packaging layers, partition coefficient k C P at the interface of outer layer and inner layer, partition coefficient k F C at the interface of inner layer and food, and mass transfer coefficient h m at the interface of inner layer and food are considered in the model. The effects of k C P, thicknesses of outer layer and inner layer, C P 0, D P, D C, k F C, and h m on the release are discussed. Corresponding conclusions and analysis are given.